STUDY ON DYNAMIC BEHAVIOR OF A NEW STEPPING-TYPE EXCAVATION,SUPPORT AND ANCHOR COMBINED UNIT AND ITS VARIABLE TEMPERATURE ENVIRONMENT - XIE Miao; LI XiaoJing; LI YuQi; WANG PengFei; ZHONG CongHua (Jixie qiangdu)
A stepping-type excavation,support and anchor combined unit in a full-mechanized excavation roadway was designed. The structure and the work principle of the unit were presented. The dynamic model of multi-degree of vibration system was established by using Newton′s second law, and the system dynamics model with temperature dependent characteristic was furtherly introduced. The simulation model of the combined system of the anchor and anchor was established by using Matlab. The dynamic behavior of the system under 20 ℃ and 40 ℃ temperature was solved and analyzed. The results showed that the temperature change environment had a great influence on the system dynamics, which made the amplitude and frequency of the system had different degrees of increase. When the system was in the environment of 20 ℃, the vibration amplitude of each part was within the acceptable range, and the vibration amplitude of the cutting part was the largest, and the range was between-12 mm to +12 mm. When the temperature increased to 40 ℃, the vibration amplitude and vibration frequency of each component were obviously increased, but the increase of the longitudinal beam was the most obvious, and the cutting part had the weakest influence.